2p+7=5-(11p+6)

Simple and best practice solution for 2p+7=5-(11p+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2p+7=5-(11p+6) equation:


Simplifying
2p + 7 = 5 + -1(11p + 6)

Reorder the terms:
7 + 2p = 5 + -1(11p + 6)

Reorder the terms:
7 + 2p = 5 + -1(6 + 11p)
7 + 2p = 5 + (6 * -1 + 11p * -1)
7 + 2p = 5 + (-6 + -11p)

Combine like terms: 5 + -6 = -1
7 + 2p = -1 + -11p

Solving
7 + 2p = -1 + -11p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '11p' to each side of the equation.
7 + 2p + 11p = -1 + -11p + 11p

Combine like terms: 2p + 11p = 13p
7 + 13p = -1 + -11p + 11p

Combine like terms: -11p + 11p = 0
7 + 13p = -1 + 0
7 + 13p = -1

Add '-7' to each side of the equation.
7 + -7 + 13p = -1 + -7

Combine like terms: 7 + -7 = 0
0 + 13p = -1 + -7
13p = -1 + -7

Combine like terms: -1 + -7 = -8
13p = -8

Divide each side by '13'.
p = -0.6153846154

Simplifying
p = -0.6153846154

See similar equations:

| 5/4+2y=4y-1/4 | | .3(6)+.05x=.15(30+x) | | lx-4l=3 | | 6x^2=12x-16/3 | | 6(v+1)-2v=2(2v+2)-11 | | 7+13y-5=9y+18-4y | | 11/6+1/5t=4 | | 3x+2x+2=9 | | 7822-3008= | | x^3-12x+35=0 | | 5k+24=k-8 | | 3x+14x+6=10 | | x-5=70 | | 9n^2+6n-3=3 | | 10x+13y=4620 | | 7/5+1/4t=5 | | 5x^2-5x-910=0 | | 4+4i/6-3i | | 7b-8=5b+4 | | -10x-19=-209 | | s=2X^2-10X+50 | | 6s^2-11s=35 | | UC=2X^2-10X+50 | | 6s^2+11s=35 | | 3y-8=6y+28 | | 168.08=2.82w+14.9 | | 6(4y-1)=18y | | 7x-1+6x+2=2x+4 | | 2x+4=7x-1 | | 3(y+1)=5y+17 | | 2(5x-11)+7=3(x-7)-15 | | 1/4(5x-4)=3 |

Equations solver categories